2011
DOI: 10.1007/s11914-011-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Bone, and Aging: An Integrative Physiology Approach

Abstract: Osteoporosis, a condition associated with significant morbidity and mortality, is prevalent in the growing elderly population. Aging is associated with characteristic changes in the complex pathways of bone remodeling and in patterns of food intake. Whereas the traditional focus of nutritional supplementation for protection of bone health has centered around calcium and vitamin D, a multitude of nutrients have been identified with effects on bone, both individually and in combination. An integrative physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 98 publications
0
27
0
2
Order By: Relevance
“…2 As the population grows older, the prevalence of osteoporosis and the incidence of osteoporosis-related fractures are becoming major social and medical concerns in both developed and developing countries. 3 Low bone mineral density (BMD) is considered a hallmark of osteoporosis as well as a valuable predictor of lowtrauma fractures. 4 The accumulation and loss of bone mass are influenced by various factors, such as age, gender, ethnicity, heredity, lifestyles (physical activity, smoking and alcohol intake) and nutritional status (calcium, protein and vitamin D intake).…”
Section: Introductionmentioning
confidence: 99%
“…2 As the population grows older, the prevalence of osteoporosis and the incidence of osteoporosis-related fractures are becoming major social and medical concerns in both developed and developing countries. 3 Low bone mineral density (BMD) is considered a hallmark of osteoporosis as well as a valuable predictor of lowtrauma fractures. 4 The accumulation and loss of bone mass are influenced by various factors, such as age, gender, ethnicity, heredity, lifestyles (physical activity, smoking and alcohol intake) and nutritional status (calcium, protein and vitamin D intake).…”
Section: Introductionmentioning
confidence: 99%
“…Osteocalcin, instead, showed a small, non-significant trend towards a reduction. Rationale to investigate novel strategies for calcium supplementation Adequate calcium supplementation is recommended for the prevention of fractures in osteoporotic patients [1,14], although recent observations suggest that a concomitant supplementation of 25(OH)D is as well required for an effective management of osteoporosis [5,6,15]. Vitamin D promotes calcium absorption with a variety of mechanisms [7], its main action being the enhancement of both the transcellular pathway-by stimulating the expression of transient receptor potential vanilloid type 6 (TRPV6) calcium channel on the apical membrane and calbindin-D 9k in the cytosol of enterocytes-and the paracellular pathway, probably by increasing tight junctions' permeability to the ion [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 can be considered a marker of bone anabolism: it is known to mediate the anabolic effects of PTH [35] and the reduction of its circulating levels is thought to have a role in the induction of sarcopenia and osteopenia [36]. Moreover, the beneficial effects of protein intake on bone mineral density [6] are mediated by an increase in IGF1 [37]. In addition, a decrease of CTx serum levels was observed, suggesting a reduction of bone resorption [38].…”
Section: Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study confirmed the importance of nutritional status for BMD, which remains in line with the findings by Gray et al 22 and Tschopp et al 23 in which low body mass index/ body weight has been linked to low BMD, especially in adolescents and young adults. It is expected that in the general adult population, 24 aging is associated with a lowering of BMD. In the present study, a tendency towards such a relationship was stated (P ¼ 0.099 for both equations).…”
Section: Discussionmentioning
confidence: 99%